An Analysis on Indonesian English Translation Shifts Found in Two Short Stories of Bilingual Children Book Series Published by Ã¢â‚¬Å“Gema InsaniÃ¢â‚¬Â - Mabruroh, Mabruroh (LUNAR, 2018)
English is international language which everyone should understand even a little. In this research, the researcher deals about translation shift especially in the bilingual children books. Indonesian is the source language while English as the target language. The objective of this research are to find out kinds of translations shift and to know how are the translation shift applied in translating two of short stories there are Ã¢â‚¬Å“Cerita Si Lebah and Cerita Si kupu-kupuÃ¢â‚¬Â. This book very interesting, many children like to read this book, because this book makes children easy to learn English. In book Cerita Si Lebah and Si Kupu-Kupu translating Indonesian into English there are a shifting. Shift is departures from formal correspondence in the process of going from SL into the TL. There are two types Translation shift they are Level Shift and Category Shift. The method of this research uses descriptive qualitative method. The data analysis used by the researcher is content analysis. The researcher read and compares both Indonesian as the source language and English as the target language. The researcher took the entire sentence from the Indonesian text and English text, check whether there are shifts in translations which are taken the valid data. Then, analyze the types of translation shifts occurred and draw conclusion based on the analysis. The objects being analyzed are books entitle Cerita Si Lebah and Cerita Si Kupu-Kupu. The researcher takes the data from thatÃ¢â‚¬â„¢s book found 22 data there are 1 data is Level Shift and 21 data is category shift. Then, from Cerita si Lebah was found 9 data, they are level shift and category shift. The category shifts found are unit shift, structure shift and class shift. From Cerita Si Kupu-Kupu book found 13 data they are category shift, they are structure shift and Intra system shift. So, it can be concluded that the translation shift found in two short are mostly category shift.